Practices, programmers, and culture of high-performance primary schools in Terengganu - Nor Azilah Husin (Fakulti pengurusan dan Ekonomi, 2012)
Terengganu state has led fifteen other states in Malaysia in a national standardized examination, UPSR for seven consecutive years starting from 2001 to 2007 (JPNT, 2007).